Endocrine disruption in a terrestrial isopod under exposure to bisphenol A and vinclozolin - Lemos, MFL
Background, aim, and scope In the past decade there has been an increasing awareness about the possible consequences of human and wildlife exposure to endocrine disrupting compounds (EDCs). Bisphenol A (BPA) and vinclozolin (Vz) are EDCs which impacts on vertebrates have been largely investigated. Nevertheless, research on invertebrate effects, especially on soil organisms, are still largely under-represented. This work aims to extend the limited ecotoxicological datasets available and to provide tools to assess the effects of EDCs on the terrestrial species, using Porcellio scaber (Crustacea: Isopoda) as a model organism. Materials and methods Male adult isopods were exposed for 10 weeks to BPA and Ronilan(R) [containing 50% Vz as active ingredient (a.i.)] at concentrations of 10, 30, 100, 300, and 1,000 mg a.i./kg of soil and compared to non-exposed isopods. We studied the effects of these EDCs on molting and total ecdysteroid (20E) concentration. Young, sexually undifferentiated isopods were also exposed to these compounds (Vz, 5, 10, 25, 50, and 100 mg a.i./kg of soil; and BPA, 10, 25, 50, 150, and 300 mg/kg of soil) for 16 weeks and effects on sex ratio were assessed. Results Exposure to both chemicals resulted in toxic effects on isopods. Time to first molt was delayed with increasing concentrations of Vz. After 10 weeks exposure to 1,000 mg a.i. Vz/kg soil, 100% mortality occurred due to incomplete ecdysis. BPA induced an opposite effect as animals started to molt sooner. Vz significantly increased the 20E titres after 7 and 14 days (LOEC 300 mg a.i. Vz/kg soil) and after 28 days of exposure the LOEC value was 100 mg a.i. Vz/kg soil. BPA also induced a 20E concentration increase after 28 days of exposure at 10, 300, and 1,000 mg/kg soil. In juveniles, we observed a low-dose alteration of sex ratio in BPA-exposed organisms with a skewed ratio of one male per two females, which is in contrast to an almost equal gender distribution in the control. Vz induced no alterations in the sex ratio of isopods. Discussion Results show that chronic Vz exposure induces a high mortality in P. scaber. This is not consistent with other studies describing non-toxicity of fungicides to arthropods. Therefore, it is desirable that toxicity assessment of fungicides is performed via chronic exposure and full life cycle tests. Previously reported low-dose responses to BPA in vertebrates are consistent with results of the present study regarding a sex-ratio shift induced by low BPA concentrations. Enhanced mortality turned out to be the effect of incomplete ecdysis related to increased ecdysteroids titres. Therefore, 'hyperecdysonism' might be a promising end-point to detect and assess endocrine disruption (ED) in arthropods inhabiting the terrestrial environment. Conclusions This work reveals that both Vz and BPA disrupt the endocrine function of these important representatives of soil edaphic invertebrates. For the first time, the existence of 'low-dose effects' affecting soil invertebrates is reported. Therefore, isopods are suitable organisms for ED assessment and endpoints such as molting, sex ratio, or 20E concentration are valuable tools for ecotoxicological studies on hormonally active substances. Recommendations and perspectives Although the effects observed in the present study have not been induced at environmentally relevant concentrations, synergistic interactions of EDC mixtures present in the environment may well have an impact on arthropods at lower substance concentrations. Additionally, the low-dose sex-ratio change demonstrated here confirms the importance of the choice for a large concentration range. The assessment of potential EDCs should consider chronic exposures and life cycle studies. Although the modes of action of EDCs in many arthropods are fragmentary, parameters like molting impairment, incomplete ecdysis, and the determination of hormone titres seem to be suitable biomarkers that should be included as soon as possible in regular surveys for the detection of hormonally active substances.